Research progress and trend of big data-driven intelligent transportation system - Chen YU; Lijuan ZHANG; Hai JIN (物联网学报)
The development of sensor technology and the popularization of sensing devices have promoted the application and development of the Internet of things.As an important part of the Internet of things,the intelligent transportation system has also made great progress,and has entered the era of data-driven from the era of technology-driven.A comprehensive and systematic literature review of the big data-driven intelligent transportation system was provided,from sensing technology and data acquisition,the data mining method and process,to various applications.The challenges faced by the big data-driven intelligent transportation system at the present stage was analyzed,and its future development trend and direction was further summarized.